Remote Sensing-Based Analysis of Urban Land Cover Changes and Surface Urban Heat Island Dynamics Using Landsat and Local Climate Zones Classification in Poznań, Poland - Aleksandra Zwolska; Marek Polrolniczak; Leszek Kolendowicz (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
Urban areas are known to experience elevated surface temperatures compared to their surrounding landscapes—a phenomenon referred to as the surface urban heat island (SUHI). The intensity of SUHI is shaped by a range of factors, among which land use and land cover (LULC) changes play a critical role. However, studies comparing SUHI conditions across extended time intervals remain limited, especially in medium-sized European cities. This study investigates how LULC changes have influenced SUHI intensity in Poznań, Poland, by comparing two periods separated by 33 years. Satellite-derived land surface temperature data from 1987–1989 and 2020–2022, combined with local climate zone (LCZ) classifications from 1988 and 2021, were used to assess spatial and seasonal SUHI dynamics. A key innovation lies in the parallel creation of LCZ classifications for both periods using tailored training areas, incorporating not only contemporary remote sensing but also archival maps and historical datasets. This approach ensures consistency in land cover assessments and enables a more accurate reconstruction of past LULC conditions. Results show a 7.4% expansion of built-up areas and a 5.6 km2 increase in hot island areas (HIAs), with the most pronounced growth in heavy industry and compact mid-rise zones. Seasonal HIA peaks shifted from spring to autumn, with the highest SUHI increases in spring (+2.8 °C) and summer (+2.5 °C). Some residential zones showed a moderating effect, with reductions of up to -0.9 °C in summer. These findings highlight the importance of climate-sensitive strategies in urban planning as cities evolve over time.